The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/pssb.201200615
|View full text |Cite
|
Sign up to set email alerts
|

Quantum critical transition from Kondo insulator to metallic state studied by band‐structure calculations for doped compounds: CeRhSb and CeNiSn

Abstract: We present the ab initio calculations of the on‐site hybridization between Ce 4f and Ce 5d electrons as well as the Mulliken Ce 5d occupation for the doped Kondo insulators CeRhSb and CeNiSn. In our investigations we have examined the following series: CeRhSb1 − xSnx, CeRh1 − xPdxSb, CeRhSb1 − xTex, Ce1 − xLaxRhSb and CeNi1 − xCuxSn, CeNiSn1 − xSbxSb, Ce1 − xLaxNiSn. The transition from the Kondo insulator to the metallic state induced by doping at some critical concentration xc was recently reported for vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…substitution of antimony by a group IV element. This has also been tested for the more complex solid solutions CeNi 1−δ Sn 1+δ−x Sb x [299] and CeRhSb 1−x Te x [300].…”
Section: Solid Solutionsmentioning
confidence: 99%
“…substitution of antimony by a group IV element. This has also been tested for the more complex solid solutions CeNi 1−δ Sn 1+δ−x Sb x [299] and CeRhSb 1−x Te x [300].…”
Section: Solid Solutionsmentioning
confidence: 99%
“…In Kondo insulators such as CeNiSn123, CeRhSb23, and Ce 3 Bi 4 Pt 3 4, interesting new physics has been proposed such as the bound states near the Kondo holes56789. With increasing concentrations of doping, an insulator-to-metal transition has been widely observed, accompanying with the change from the dense Kondo lattice regime to the single-ion Kondo regime.…”
mentioning
confidence: 99%
“…Transition from KI in CeRhSb to a metallic state in CeRhSn via the critical point was studied by means of density functional theory (DFT) calculations before [26]. It was shown that QPT is manifested by a change of Mulliken occupation of Ce 5d states as a function of x.…”
Section: Introductionmentioning
confidence: 99%